Orphan nuclear receptor 4A1 (NR4A1) and novel ligands. Issue 6 (26th November 2021) - Safe, Stephen; Shrestha, Rupesh; Mohankumar, Kumaravel
Abstract: The nuclear receptor (NR) superfamily of transcription factors encodes expression of 48 human genes that are important for maintaining cellular homeostasis and in pathophysiology, and this has been observed for all sub-families including orphan receptors for which endogenous ligands have not yet been identified. The orphan NR4A1 (Nur77 and TR3) and other members of this sub-family (NR4A2 and NR4A3) are immediate early genes induced by diverse stressors, and these receptors play an important role in the immune function and are up-regulated in some inflammatory diseases including solid tumors. Although endogenous ligands for NR4A have not been identified, several different classes of compounds have been characterized as NR4A1 ligands that bind the receptor. These compounds include cytosporone B and structurally related analogs, bis-indole derived (CDIM) compounds, the triterpenoid celastrol and a number of other chemicals including polyunsaturated fatty acids. NR4A1 ligands bind different regions/surfaces of NR4A1 and exhibit selective NR4A1 modulator (SNR4AM) activities that are dependent on ligand structure and cell/tissue context. NR4A1 ligands exhibit pharmacologic activities in studies on cancer, endometriosis metabolic and inflammatory diseases and are promising agents with clinical potential for treating multiple diseases.